Kehidupan Masyarakat Pulau Salissingan Sulawesi Barat (1994-2009) - Yusran Yusran; Jamil Jamil; Muhammad Azmi (History Education Department, Universitas Mulawarman, 2022)
This study aims to explain the history of the development of the life of the people of Salissingan Island which is seen in three aspects, namely the political aspect, the economic aspect, and the social aspect. Then the type of research used is historical research which consists of Heuristics, Criticism, Interpretation and Historiography. The focus of this research is community life and the development of community life on Salissingan Island. The results of this study indicate that the development of community life on Salissingan Island refers to three aspects, namely the Political Aspect regarding the formation of the first village in 1994 and then in 2008 the second village was formed. next On the economic aspect of people's lives seen in the work as fishermen and fishermen's income in the form of sea cucumbers and lobster shrimp. as for the social aspect regarding the development and population growth of Salissingan Island since 1994-2009